Associations between dietary patterns and 10-year cardiovascular disease risk score levels among Chinese coal miners--a cross-sectional study - Qian Sun; Jin-Sha Ma; Hui Wang; Shu-Hong Xu; Jun-Kang Zhao; Qian Gao; Jian-Jun Huang; Tong Wang (BMC, 2019)
Abstract Background Diet-related cardiovascular diseases have produced a large health burden in China. Coal miners are a high-risk population for cardiovascular disease, but there is little evidence concerning associations between coal miners' dietary patterns and their 10-year cardiovascular disease risk score levels. Methods The study included 2632 participants and focused on dietary patterns associated with higher 10-year cardiovascular disease risk score levels. A valid semi-quantitative food frequency questionnaire was used to collect data regarding dietary intake, and dietary patterns were identified using factor analysis combined with cluster analysis. Logistic regression was used to assess associations between dietary patterns and 10-year cardiovascular disease risk score levels. Results For ground workers, compared with the 'Healthy' pattern, the 'High-salt' and 'Refined grains' patterns were significantly associated with higher 10-year atherosclerotic cardiovascular disease risk score level (OR: 1.50, 95% CI: 1.02-2.21; OR: 1.92, 95% CI: 1.26-2.93) and 10-year ischemic cardiovascular disease risk score level (OR: 2.18, 95% CI: 1.25-3.80; OR: 2.64, 95% CI: 1.48-4.72) adjusted for gender, and behavioural and socioeconomic factors. The 'High-fat and salt' pattern was significantly associated with higher 10-year ischemic cardiovascular disease risk score level (OR: 1.97, 95% CI: 1.13-3.42). For underground workers, the 'High-salt' pattern was significantly associated with higher 10-year atherosclerotic cardiovascular disease risk score level (OR: 1.65, 95% CI: 1.16-2.36) and 10-year ischemic cardiovascular disease risk score level (OR: 1.76, 95% CI: 1.09-2.84). Conclusions This study provides evidence for dietary patterns associated with higher 10-year cardiovascular disease risk score levels in Chinese miners, and facilitates relevant departments in designing effective dietary guidelines to ameliorate dietary structures.